2010
DOI: 10.1555/mars.2010.0005
|View full text |Cite
|
Sign up to set email alerts
|

Pancam and Microscopic Imager observations of dust on the Spirit Rover: Cleaning events, spectral properties, and aggregates

Abstract: Approach: The Mars Exploration Rover Spirit has experienced over 2000 martian days (sols) of interaction w ith the martian dust c ycle. Much d ust accumulated o n the vehicle, but there have also been t hree major "cleaning e vents" when s ignificant a mounts o f d ust w ere removed. Pa ncam d ust monitoring observations acquired every ~10 sols throughout the mission allowed visual inspection of the amount of dust collecting on a portion of the solar array and on the Pancam and Mini-TES calibration targets. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 34 publications
(68 reference statements)
5
40
0
Order By: Relevance
“…Assuming dust lifting occurs over the footprint of the devil (or at least over some region that scales with diameter -an annulus near the dust wall perhaps) then for a fixed advection speed a given spot of ground will endure a longer scouring period for a Table 1 Dust clearing events documented on the Spirit rover (derived from Vaughan et al, 2010) and dust devils observed from the rover . Fig.…”
Section: Comparison With Dust Devil Tracksmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming dust lifting occurs over the footprint of the devil (or at least over some region that scales with diameter -an annulus near the dust wall perhaps) then for a fixed advection speed a given spot of ground will endure a longer scouring period for a Table 1 Dust clearing events documented on the Spirit rover (derived from Vaughan et al, 2010) and dust devils observed from the rover . Fig.…”
Section: Comparison With Dust Devil Tracksmentioning
confidence: 99%
“…The much longer operation of these vehicles was made possible by unanticipated 'dust clearing events' (e.g. Vaughan et al, 2010) which are interpreted to be wind gusts or dust devils which removed much of the dust that had accumulated. Clearly, the existence of such events has a dramatic effect on the longevity and productivity of solar-powered missions, and thus they demand to be better understood.…”
Section: Introductionmentioning
confidence: 99%
“…Arvidson et al (2006a) and Arvidson et al (2008) provided an overview of key observations of soils and rocks. Along the traverse in the Gusev plains ( Figure 2), images showed that the soil is composed of: (i) basaltic material excavated from lava flows by local impacts (Greeley et al, 2005a), (ii) a layer of dark coarse sands and granules (0.5 to a few mm in diameter) (Herkenhoff et al, 2004a;Herkenhoff, K. E., et al, 2006) (Figure 2c, top), interpreted to be rich-olivine basalts (Bell et al, 2004;Christensen et al, 2004;McSween, H. Y. et al, 2004), (iii) subangular lithic fragments, interpreted to be ejecta deposits, which are associated with the numerous craters, composed of clasts and rocks, and (iv) all coated with bright fine-grained materials, inferred to be dust with particles from silt (< 4 µm in diameter) (Lemmon et al, 2004) to fine sand (mostly less than 150 µm), forming dust aggregates, (Herkenhoff et al, 2004a;Sullivan et al, 2008;Vaughan et al, 2010) (Figure 2c The ω values estimated from CRISM (ω CRISM 0.65 − 0.75) are compared to those estimated from Pancam measurements at 753 nm, located in our "dark-linear feature" geological unit, for different geological units (rocks and soils) (Johnson et al, 2006a) (Figure 4a). The ω values are consistent with those obtained at Bonneville Rim site (ω P ancam 0.66), Landing Site and NW of Missoula areas (ω P ancam 0.75).…”
Section: Geological Context and Study Areasmentioning
confidence: 99%
“…However, during the duststorms, dust grains up to a few tens of micrometres in diameter can be also lifted into the atmosphere (Greeley and Iversen, 1985). Over shorter scales even much larger grains up to 200 lm can be transported, mainly by saltation (Vaughan et al, 2010).…”
Section: Values Of Parametersmentioning
confidence: 99%